Stereotactic body radiotherapy for second primary lung cancer and intra-parenchymal lung metastasis in patients previously treated with surgery: evaluation of indications and predictors of decreased respiratory function. (2nd September 2018) - Ishihara, Takeaki; Yamada, Kazunari; Harada, Aya; Yukiue, Haruhiro; Tanahashi, Masayuki; Niwa, Hiroshi; Matsui, Takashi; Yokomura, Koshi; Ejima, Yasuo; Sasaki, Ryohei
Abstract: Background: The adaptation criteria for administration of stereotactic body radiotherapy (SBRT) to patients with lung cancer who previously underwent surgery and subsequently developed a second primary lung cancer (SPLC) or intra-parenchymal lung metastasis (IPLM) are controversial, unlike the criteria for repeat surgery. We aimed to evaluate the feasibility of SBRT for these patients. Factors associated with decreased respiratory function were also evaluated. Material and methods: Sixty-nine patients with 89 lesions who underwent SBRT between 2008 and 2017 were analyzed. Of these, 29 were diagnosed with SPLC while the remaining 40 had IPLM. The distribution of histological types was as follows: squamous cell carcinoma ( n  = 13 lesions); adenocarcinoma ( n  = 25); non-small cell carcinoma ( n  = 1); unknown histological type ( n  = 49). The prescribed doses to the planning target volume (PTV) were 50 Gy in five fractions for 85 lesions and 60 Gy in 10 fractions for four lesions at PTV mean. Results: Over a median follow-up period of 55 months, the 4-year overall survival and local control rates were 50.3% and 87.6%, respectively. Six patients experienced grade 2 radiation pneumonitis and one experienced grade 3. Two patients experienced grade 5 pulmonary fibrosis. Decreased respiratory function was observed in 10 patients (15.1%). On multivariate analysis, the presence of pulmonary disease before SBRT was the only statistically significant factor associated with decreased respiratory function. Conclusions: SBRT is safe and feasible in patients with SPLC or IPLM previously treated surgically. Pre-existing pulmonary disease was a predictive factor for decreased respiratory function.